Precondicionant factors of sequela in children under 5 years with congenital muscular wryneck - Pablo Antonio Hernández Dinza; Yaimet Pérez Infante; Vivianne Castro Correoso; Yanet Henriquez García (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The spectrum of sequela of the congenital muscular wryneck is wide. Some children with these sequela require expensive and complex operations.  Objective: To determine the precondicionant factors associated with organic sequela of the congenital muscular wryneck in patients since one month to 5 years.  Methods: A retrospective, analytic, non experimental of cases and controls study was carried out that included children with diagnosis of congenital muscular wryneck, assisted in the Neurodevelopment Service of Antonio María Beguez Cesar Children Hospital in Santiago de Cuba, from January, 2017 to December, 2020. The group of cases was conformed by all the patients with organic complications of the congenital muscular wryneck (24 children) and the control group, for those who didn't present these complications (72), selected by means of a simple random sampling.  Results: The male sex prevailed in the patients with complications (62.5 %). The plagiocephaly and the facial asymmetry were the most frequent sequela. The age under 6 months in the moment of the diagnosis of the entity constituted a protective factor (OR = 0.12; IC 95 %: 0.04-0.33; p=0.000); there was association of the complications with the dystocic childbirth (OR = 0.36; IC 95 %: 0.13-1.01; p=0.049) and with the fetal macrosomia (OR = 5.7; IC 95 %: 1.44-22,2; p=0.014). There was also highly significant association of the complications with the asymmetry of both sternocleidomastoid muscles (OR = 11.4; IC 95 %: 3.7-34.9; p=0-000) and with the late beginning of the treatment (OR = 8.5; IC 95 %: 3.0-24.1; p=0.000).  Conclusions: The dystocic childbirth,  fetal macrosomia,  asymmetry between both sternocleidomastoid muscles and the late beginning of the rehabilitative treatment increased the risk of complications in the members of the case material.